THE EFFECT OF MOBILE APPLICATION-BASED NUTRITION EDUCATION ON DIABETES KNOWLEDGE AND BLOOD GLUCOSE LEVELS IN PATIENTS WITH TYPE II DIABETES MELLITUS IN THE WORKING AREA OF BELIMBING PUBLIC HEALTH CENTER : MOBILE APPLICATION-BASED NUTRITION EDUCATION - Amelia, Aurora Andari; Azrimaidaliza, Azrimaidaliza; Elnovriza, Deni (STIKes Mandala Waluya Kendari, 2025)
Background: Diabetes remains the most prevalent non-communicable disease (NCD) in Padang City, with the highest case burden reported at Belimbing Health Centre (74.3%, or 998 cases). This study aimed to evaluate the effect of mobile-based nutrition education on diabetes knowledge and blood glucose control among patients with type 2 diabetes mellitus. Methods: A quasi-experimental design was employed involving 66 respondents, using a pre-test–post-test with control group design. Participants were selected through simple random sampling, and the intervention was conducted from December 2024 to July 2025. Data analysis was performed using univariate and bivariate methods. Results: The intervention demonstrated statistically significant improvements in all outcome variables within the intervention group. The proportion of respondents with good diabetes knowledge increased from 0.0% to 90.9% (p < 0.001) and normal blood glucose levels rose from 27.3% to 81.8% (p < 0.001). In contrast, the control group showed no statistically significant changes across all variables (p > 0.05). Conclusion: In conclusion, mobile-based nutrition education is effective in improving diabetes knowledge, promoting adherence to recommended dietary patterns, and achieving better glycemic control. This approach represents a practical and scalable educational intervention for supporting self-management of type 2 diabetes mellitus, particularly in primary care settings.